2017
DOI: 10.1152/ajprenal.00592.2015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of endurance training and branched-chain amino acids on the signaling for muscle protein synthesis in CKD model rats fed a low-protein diet

Abstract: A low-protein diet (LPD) protects against the progression of renal injury in patients with chronic kidney disease (CKD). However, LPD may accelerate muscle wasting in these patients. Both exercise and branched-chain amino acids (BCAA) are known to increase muscle protein synthesis by activating the mammalian target of rapamycin (mTOR) pathway. The aim of this study was to investigate whether endurance exercise and BCAA play a role for increasing muscle protein synthesis in LPD-fed CKD (5/6 nephrectomized) rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Regular exercise exerts a positive effect on muscle mass in CKD by enhancing protein synthesis and suppressing proteolysis via UPS activation (Bacurau et al., 2016; De Moraes et al., 2018; Sakai et al., 2017; Yoshida et al., 2017). For instance, exercise has been found to increase PGC‐1α mRNA expression, a master regulator of mitochondrial biosynthesis and energy metabolism (Cantó & Auwerx, 2009; Wu et al., 1999).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Regular exercise exerts a positive effect on muscle mass in CKD by enhancing protein synthesis and suppressing proteolysis via UPS activation (Bacurau et al., 2016; De Moraes et al., 2018; Sakai et al., 2017; Yoshida et al., 2017). For instance, exercise has been found to increase PGC‐1α mRNA expression, a master regulator of mitochondrial biosynthesis and energy metabolism (Cantó & Auwerx, 2009; Wu et al., 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Since BCAA may cause glomerular hyperfiltration and aggravate renal prognosis (Pillai et al., 2019), few studies have examined the effect of BCAA alone on muscle in renal injury models. Yoshida et al reported (Yoshida et al., 2017) that BCAA administration alone was ineffective against CKD‐induced muscle wasting in 5/6 nephrectomized rats, but had a synergistic effect with exercise without the progression in CKD. Similarly, in a human study, BCAA, when used in combination with exercise, enhanced phosphorylation of mammalian target of rapamycin (mTOR) complex 1 and ribosomal protein S6 kinase (S6K) beta‐1, and decreased atrogin‐1 and MuRF‐1 mRNA levels, in vastus lateralis muscle (Borgenvik, Apró, & Blomstrand, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations